Battery plug - in electric car : Vehicle chassis components design and modification - Tow, Edward (2015)
Electric powered vehicles have been in existence for nearly 100 years. The rise in popularity today for many are perhaps of the same reasons when they were first popular. Now that leading manufacturers have hopped on the electric bandwagon, it is only a matter of time before electric powered vehicles ply the city streets. Singapore has invited many technopreneurs around the world to help develop a “Smart Nation”. It is only timely to have local university, Nanyang Technological University (NTU) own an electric car for purposes of research and development. This project applies engineering processes and theories learnt during the mechanical engineering course. Disclosed within the report are the refurbishment work done on the Battery Electric Vehicle (BEV), the design, analysis and fabrication of brackets to mount specific components, and lastly the fabrication of chassis beams. Through this hands-on project, the author has gathered lessons and experience working in an automotive platform, and has gained more confidence in automotive repairs. The future of the BEV project is discussed in the last segment.